Exploring senior managers' perceptions of the COVID-19 Crisis in Iran: a qualitative content analysis study - Mostafa Bijani; Shahnaz Karimi; Aliasghar Khaleghi; Yousef Gholampoor; Zhila Fereidouni (BMC, 2021)
Abstract Background Identification of the experience of senior managers in tackling biological crises can be a roadmap for future crisis management planning. The aim of the present study was to investigate the experiences of senior managers during the COVID-19 crisis. Methods This is a descriptive qualitative research. Data were collected using in-depth and semi-structured individual interviews. Accordingly, 20 senior managers of medical universities with experience in managing the COVID-19 crisis were enrolled in the study using purposive sampling. Data were collected from February 2020 to May 2021. For data analysis, qualitative content analytical approach was used. Results According to the results, 4 main themes and 10 sub-themes were obtained; they included dealing with issues and challenges in the face of COVID-19 disease (Structural challenges, Cultural challenges, Educational challenges, COVID-19 complexity); individual and managerial competencies (Individual competencies, Managerial competencies); comprehensive, accountable, and efficient management (Comprehensive and accountable management, efficient management); and professional and organizational self-efficacy (Professional self-efficacy, organizational self-efficacy) were obtained. Conclusions In the present study, a number of senior managers' experiences in the COVID-19 crisis management were identified. Managers and policymakers of the health system are suggested to use the results of the present study to effectively manage the crisis and improve crisis management in various health-related areas by providing an effective cultural and organizational context.